On the thrust performance of a flapping two-dimensional elliptic airfoil in a forward flight. (October 2016) - Lua, K.B.; Dash, S.M.; Lim, T.T.; Yeo, K.S.
Abstract: In this paper, results of numerical and experimental studies are presented for a flapping two-dimensional (2D)elliptic airfoil in a forward flight condition at a Reynolds number of 5000.The study is motivated by the experiment of Read et al. (2003), which shows that the thrust coefficient of a 2D NACA0012 airfoil deteriorated at high flapping frequency (or Strouhal number) when the induced effective angle of attack profile ceases to be a simple harmonic function in time. As to why non-simple-harmonic profile of effective angle of attack is detrimental to thrust generation is not fully understood. The paper is an attempt to address this issue by examining the flow mechanism, including near field flow structures and the associated transient aerodynamic forces and pressure field, responsible for the observed behavior. Our results show that thrust suppression can be attributed to an adverse suction effect due to high rotation rate of the airfoil and the presence of an attached leading edge vortex generated in the previous stroke. The results further show that the condition for best efficiency need not necessary coincides with the condition of best thrust performance; this observation has been made in past studies of flapping flight.